Determinants of Low Birth Weight in Cilacap District - Septikasari, Majestika (Journal of Maternal and Child Health, 2020)
Background: Low birth weight (LBW) is closely related to the increased risk of child morbidity and mortality, disruption of developmental growth and in the long-run has an increased risk of chronic disease in their adulthood. This study aims to analyze the effect of nutritional status at the beginning of pregnancy, maternal education and family expenditure on the incidence of low birth weight (LBW) in Cilacap District.Subjects and Method: This study is an observational analytic study with a cross sectional approach. The study was conducted in three health centers in Cilacap District, Central Java, in 2016. A sample of 144 children aged less than 1 year was selected by cluster sampling. The dependent variable was birth weight. The independent variables were maternal MUAC, maternal education, and family income. The data are collected with medical records. The data were analyzed using multiple logistic regression analysis.Results: Maternal MUAC ≥23.5 cm (OR = 0.22; 95% CI = 0.57 to 0.89; p = 0.033) reduced the risk of LBW and it was statistically significant. Maternal education (OR = 0.51; 95% CI = 0.12 to 2.13; p = 0.356) and high family income (OR = 0.47; 95% CI = 0.09 to 2.47; p = 0.376) reduced the risk of LBW but it is statistically insignificant.Conclusion: Maternal MUAC ≥23.5 cm, high maternal education, and high family income reduced the risk of LBW.Keywords: low birth weight, maternal mid-upper arm circumferenceCorrespondence: Majestika Septikasari. School of Health Sciences Al-Irsyad Al-Islamiyyah Cilacap, Central Java, Indonesia. Email: majestika86@gmail.com.Journal of Maternal and Child Health (2020), 5(2): 141-146https://doi.org/10.26911/thejmch.2020.05.02.03